Examining The Role of Learning Interest In Shaping Elementary Students’ Science Achievement: A Systematic Literature Review - Mardin, Laode; Sumianti, Wa Ode Siti (SEARCH: Science Education Research Journal, 2025)
This study aims to examine the role of learning interest in shaping science learning achievement among elementary school students through a systematic literature review approach. The study employed a Systematic Literature Review (SLR) method by analyzing relevant articles published between 2015 and 2025, sourced from Google Scholar and Garuda databases. A total of 45 articles were initially identified, and after applying inclusion and exclusion criteria, 20 articles were selected for further analysis. The data were analyzed using a qualitative descriptive approach through narrative synthesis. The findings reveal that 80% of the reviewed studies indicate a significant positive relationship between learning interest and science learning outcomes. Students with higher levels of learning interest tend to demonstrate greater engagement, stronger motivation, and better academic performance. However, the results also show that the influence of learning interest is not independent, as it is affected by other factors such as instructional strategies, learning media, and the learning environment. In conclusion, learning interest plays a crucial role in improving science learning outcomes among elementary school students. Nevertheless, its effectiveness depends on the integration of innovative teaching strategies and supportive learning conditions. This study highlights the importance of enhancing students’ learning interest through interactive and student-centered learning approaches.